The first experience of lengthening enteroplasty for short bowel syndrome in a one-month-old baby in Ukraine - O.K. Sliepov; M.Y. Migur; O.P. Ponomarenko; O.P. Gladyshko; O.V. Markevich; G.О. Grebinichenko (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2020)
Closed gastroschisis is one of the rarest forms of gastroschisis, in which the prolapsed organs are pinched in a stenotic defect of the anterior abdominal wall. This leads to the development of local or total compression infarction of the eventrated midgut and the development of short bowel syndrome. Surgical treatment of this pathology is complex and multi-stage, and presents great difficulties for pediatric surgeons around the world. Case report. Assumption of closed gastroschisis is established prenatally. 10 minutes after the birth, an operation was performed: mobilization and reduction of eventrated organs with primary fascial abdominoplasty. At the same time, no reliable signs of intestinal obstruction were found. On the 5th day of life, Mikulicz enterostomy was performed for the diagnosed atresia of the jejunum. On the 32nd day of life, the final stage of surgical management was performed: relaparotomy, adhesiolysis, enterostomy, narrowing and lengthening of the jejunum with serial transverse enteroplasty procedure. At the age of 1.5 months, the child achieved complete enteral autonomy. The proposed tactics and strategy of surgical treatment is effective, made it possible to lengthen the small intestine and maintain the absorption surface of the mucosa in order to achieve full enteral autonomy. Level of evidence - V. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of an participating institution.The informed consent of the child's parents was obtained from the studies.